2010
DOI: 10.1016/j.jconrel.2010.07.116
|View full text |Cite
|
Sign up to set email alerts
|

Polymer particle shape independently influences binding and internalization by macrophages

Abstract: The interaction of macrophages with micro and nano particles (MNPs) is important because these cells clear particles from the circulation, and because they are potential therapeutic targets in inflammatory conditions, atherosclerosis and cancer. Therefore, an understanding of the features of MNPs that influence their interaction with macrophages may allow optimization of their properties for enhanced drug delivery. In this study, we show that particle shape impacts phagocytosis by macrophages, and more importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
301
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(316 citation statements)
references
References 38 publications
10
301
2
3
Order By: Relevance
“…Probably, the lower aspect ratio of oblate ellipsoids is related with less actin rearrangement and a faster/more effi cient internalization. [ 100 ] The effect of the shape on endocytosis by HeLa cells (from cervical cancer) was studied using cubic and cylindricalshaped PEG hydrogel particles obtained by particle replication in non-wetting templates. [ 101 ] Cubic particles with side lengths of 3 and 4 µm were not internalized whereas with 2 µm they were internalized by most cells.…”
Section: Effect On Internalization and Traffi Ckingmentioning
confidence: 99%
“…Probably, the lower aspect ratio of oblate ellipsoids is related with less actin rearrangement and a faster/more effi cient internalization. [ 100 ] The effect of the shape on endocytosis by HeLa cells (from cervical cancer) was studied using cubic and cylindricalshaped PEG hydrogel particles obtained by particle replication in non-wetting templates. [ 101 ] Cubic particles with side lengths of 3 and 4 µm were not internalized whereas with 2 µm they were internalized by most cells.…”
Section: Effect On Internalization and Traffi Ckingmentioning
confidence: 99%
“…[69] Similarly, Sharma et al showed a profound impact of the particle shape on phagocytosis of PS particles by macrophages, where oblate ellipsoids were more easily internalized than prolate ellipsoids or spheres. [70] Cell attachment and internalization were influenced independently by particle shape. Prolate ellipsoids showed the highest cell attachment, but the lowest internalization rate after binding to cells, while oblate ellipsoids had the highest internalization rate after attaching but a lower overall cell attachment.…”
Section: Effects Of Particle Properties On Bio-nano Interactionsmentioning
confidence: 99%
“…Prolate ellipsoids showed the highest cell attachment, but the lowest internalization rate after binding to cells, while oblate ellipsoids had the highest internalization rate after attaching but a lower overall cell attachment. [70] Shimoni et al reported that the human cervical cancer cell line HeLa displayed a preference for spherical polymeric capsules compared with rod-like capsules. [71] The polymeric rod-shaped capsules exhibited lower and slower cellular internalization with increasing aspect ratio (AR).…”
Section: Effects Of Particle Properties On Bio-nano Interactionsmentioning
confidence: 99%
“…Enhanced cellular uptake has also been demonstrated as a consequence of imbuing NVs with non-spherical shapes, which needs to be investigated more extensively in order to give more extensive understanding [25]. Moreover, particle shape has been identified as a critical factor in particle uptake by phagocytes, with non-spherical morphologies giving rise to a range of behaviours [75,76]. It has also been demonstrated that the aspect ratio of rod-like NPs impacts cellular internalization, with different pathways being triggered depending upon the particle length [77].…”
Section: Impact Of Nanovector Morphology On Performance In Vitro and mentioning
confidence: 99%